The Association between White Blood Call with CD59 Expression upon surface in Peripheral blood and Therapeutic Response to Anti-CD20 Antibody in B-Non Hodgkin’s Lymphoma - Taengdaen, sirikajorn; Rojnuckarin, Ponlapat; Intragumtornchai, Tanin (Maharat Nakhon Ratchasima Hospital Journal, 2024)
Background: Although Rituximab is effective treatment for B-cell non-Hodgkin lymphoma, the exact mechanism of its antitumor effect is unclear. One potential mechanism involves complement-mediated cytotoxicity. The usage of rituximab should be considerably selected because it is vary expensive. Objective: To assess the association between expressions of CD59 on white blood cell surface in peripheral blood and outcome after chemotherapy in combination with rituximab treatment in B-cell non-Hodgkin lymphoma patients. Patients & Methods: Patients with B-cell non-Hodgkin lymphoma who received treatment with rituximab plus chemotherapy at King Chulalongkorn Memorial Hospital from August 2001 to October 2002 who gave informed consent, were recruited to the study. The patients had received physical examination, blood test, radiographic examination, bone marrow study and the expression of CD59 on white blood cell surface in peripheral blood was determined by flow cytometry before rituximab treatment. Patients were classified as achieved complete responses (CR) or no compete response after complete treatment. Result: A total of 47 B-cell NHL patients were included in the study. The median age of the patents was 53 ± SD year (range 20-77). The histology subtypes were diffuse large B-cell follicular small cleave, and small lymphocytic 89.4%, 8.5% and 2.1%, respectively. The frequencies of patients in low, low-intermediate, high-intermediate and high risk groups according to the international prognostic index were 8.5%, 19.1%, 29.8% and 42.6%, respectively. Twenty-five patients (53.2%) received rituximab plus CHOP. Thirty-six patients achieved complete responses (CR), 11 patients obtained no CR. Mean CD59 level were not significantly higher in non CR group than in CR group (55.3%, 40.57%) (P-value=0.13). Conclusion: Expression of CD59 on white blood cell surface in peripheral blood dose not predict clinical outcome after rituximab treatment in B-cell non-Hodgkin lymphoma.